This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Rewrite the following equation as: 2 x 2 + 8 y 2 − 4 x y − 4 x − 8 y − 1 6 = 0
After that, it can be written as: ( x − 2 ) 2 + ( x − 2 y ) 2 + ( 2 y − 2 ) 2 = 2 4
Now, assume that 2 4 = a 2 + b 2 + c 2 with a ≥ b ≥ c . Then 4 ≥ a ≥ 3 otherwise the sum gets too high or low. Applying a = 3 , we get b 2 + c 2 = 1 5 . But 15 is of the form 4 m + 3 . Therefore, no solution. Applying a = 4 , we get b 2 + c 2 = 8 . We see that b = c = 2 . Therefore, ( a , b , c ) = ( 4 , 2 , 2 ) , ( − 4 , − 2 , − 2 ) , ( − 4 , 2 , 2 ) , ( − 4 , − 2 , 2 ) , ( 4 , − 2 , − 2 ) , ( 4 , 2 , − 2 ) .
Now, we have various cases. Doing some amount of casework will give you the following pairs x , y : ( − 2 , 0 ) , ( 0 , − 1 ) , ( 0 , 2 ) , ( 4 , 0 ) , ( 4 , 3 ) , ( 6 , 2 )